Newsletter Institute of Medical Molecular Biotechnology Issue 10 August 2021 / Institute of Medical Molecular Biotechnology - Universiti Teknologi MARA, Institute of Medical Molecular Biotechnology (Institute of Medical Molecular Biotechnology, 2021)
The Institute of Medical Molecular Biotechnology (IMMB) at Universiti Teknologi MARA (UiTM) launched its inaugural newsletter in November 2020. This publication serves as a platform to disseminate the institute's latest research activities, events, and achievements to the scientific community and the public.